Review of the LIBER “Think Tank on the future value of the book as artefact and the future value of digital documentary heritage”, National Library of Sweden, Stockholm, Sweden, 24-25 May 2007 - Langendoen, Andrea; Schouten, Dennis; Shenton, Helen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
What is the future of the book, or maybe rather, does the book have a future at all? These are questions that are raised again and again within different disciplines in the digital age, from e-strategists to historical bibliographers. During a two-day Think Tank, held at the Swedish National Library at Stockholm on May 24-25, authors, critics, scholars, representatives of libraries, archives and other heritage institutions and knowledge organizations tried to find answers to these and other related questions, such as: do the concepts of ‘value’ and ‘authenticity’, which are based on physical objects still have any meaning? Does digitisation decrease or increase the value of the book as an artefact? Will the rapid growth of digitised and born-digital publications lead to a new digital cultural heritage? Indeed, has the critical mass of ‘born digital’ and digitised material already created a new digital cultural documentary heritage?